Integration Of Life Skills Through Hockey In The Framework Of Positive Youth Development - Muhammad Suma Wijaya; Yusuf Hidayat; Nina Sutresna (JUARA : Jurnal Olahraga, 2023)
This study aims to find out how much influence the integration of life skills has on youth hockey in the city of Bandung. Development of life skills in the context of Positive Youth Development, to find out which components of life skills have experienced the highest increase, and to find out how much life skills contribute to Positive Youth Development. The research method used is an experiment with a Quasi-Experimental Design model. The data collection techniques used in this study were the LSSS and CPYDS questionnaires. The sampling technique used purposive sampling. The number of samples was 30 youths who took part in extracurricular hockey, which were divided into two groups: hockey training, which was given the integration of life skills consisting of 15 kids, and Hockey training, which was not given life skills integration composed of 15 children. Research Results There is a significant effect of the integration of life skills in the development of youth hockey on life skills in the framework of Positive Youth Development. There is a substantial influence of non-integrated life skills in the development of youth hockey on life skills in the context of Positive Youth Development. There is a difference in the effect of hockey training integrated life skills and non-integrated life skills on developing life skills in the framework of Positive Youth Development. Integrated life skills hockey training is better than non-integrated life skills. The components of life skills that experienced the highest increase in the integrated life skills group were interpersonal communication and social skills. Meanwhile, the life skills component that experienced the highest growth in the non-integrated life skills group was teamwork. There is a contribution to life skills and positive youth development (PYD).